ANALYSIS OF CAPITAL EXPENDITURE DETERMINANTS IN DISTRICTS/CITIES IN JAMBI PROVINCE - Karim, M; Antoni, Syafrul; Oktarina, Karlini (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
Regional Expenditures are details of regional income and expenditures within one year. Capital expenditure is one of the most important components of regional expenditures. Through capital expenditure, the budget prepared in the Regional Expenditures can be realized properly and correctly by improving services to the public. In this case, regional governments must be careful when allocating their resources. This research aims to analyze the influence of local revenue, general allocation funds, and special allocation funds on capital expenditure allocation. Capital expenditure plays a very important role in running the government system to improve community welfare and good governance. The population used in this research is all 11 regencies/cities in Jambi Province in 2018-2022. The sample in this research is this population due to data availability, while the data analysis technique used is multiple linear regression—analysis using SPSS. The research results show that local original income has a significant and positive effect on capital expenditure allocation, general fund allocation has no effect on capital expenditure, and special fund allocation also has no effect on capital expenditure. In contrast, local original income, General Allocation Funds, and special allocation funds simultaneously significantly impact capital expenditure allocation.